Can PBDEs affect the pathophysiologic complex of epithelium in lung diseases?. (February 2020) - Albano, Giusy Daniela; Moscato, Monica; Montalbano, Angela Marina; Anzalone, Giulia; Gagliardo, Rosalia; Bonanno, Anna; Giacomazza, Daniela; Barone, Rosario; Drago, Gaspare; Cibella, Fabio; Profita, Mirella
Abstract: Brominated flame-retardant (BFRs) exposure promotes multiple adverse health outcomes involved in oxidative stress, inﬂammation, and tissues damage. We investigated BFR effects, known as polybrominated diphenyl ethers (PBDEs) (47, 99 and 209) in an air-liquid-interface (ALI) airway tissue derived from A549 cell line, and compared with ALI culture of primary human bronchial epithelial cells (pHBEC). The cells, exposed to PBDEs (47, 99 and 209) (0.01–1 μM) for 24 h, were studied for IL-8, Muc5AC and Muc5B (mRNAs and proteins) production, as well as NOX-4 (mRNA) expression. Furthermore, we evaluated tight junction (TJ) integrity by Trans-Epithelial Electrical Resistance (TEER) measurements, and zonula occludens-1 (ZO-1) expression in the cells, and pH variations and rheological properties (elastic G′, and viscous G″, moduli) in apical washes of ALI cultures. N-acetylcysteine (NAC) (10 mM) effects were tested in our experimental model of A549 cells. PBDEs (47, 99 and 209) exposure decreased TEER, ZO-1 and pH values, and increased IL-8, Muc5AC, Muc5B (mRNAs and proteins), NOX-4 (mRNA), and rheological parameters (G′, G″) in ALI cultures of A549 cell line and pHBEC. NAC inhibited PBDE effects in A549 cells. PBDE inhalation might impairs human health of the lungs inducing oxidative stress, inflammatory response, loss of barrier integrity, unchecked mucus production, as well as altered physicochemical and biological properties of the fluids in airway epithelium. The treatment with anti-oxidants restored the negative effects of PBDEs in epithelial cells. Highlights: ALI culture is an appropriate in vitro model to assess pulmonary toxicity of PBDEs. PBDE exposure promote oxidative stress in airway epithelium. PBDE exposure increase inflammation and mucus hypersecretion in airway epithelium. PBDE inhalation impair the integrity of epithelial layer. PBDE pollution affect airway diseases.